1993
DOI: 10.2337/diab.42.7.981
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox Between Resistance to Hypoxia and Liability to Hypoxic Damage in Hyperglycemic Peripheral Nerves: Evidence for Glycolysis Involvement

Abstract: Isolated ventral and dorsal rat spinal roots incubated in normal (2.5 mM) or high glucose (25 mM) concentrations or in high concentrations of other hexoses were exposed transiently to hypoxia (30 min) in a solution of low buffering power. Compound nerve action potentials, extracellular direct current potentials, and interstitial pH were continuously recorded before, during, and after hypoxia. Ventral roots incubated in 25 mM D-glucose showed resistance to hypoxia. Dorsal roots, on the other hand, revealed elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…It has been reported that the fast K + channel activity is reduced by 50% at cytoplasmic pH of 6.8 as a result of enhanced anaerobic glycolysis [24,48]. Decreased K channels could also explain our finding of membrane depolarization.…”
Section: Na and K Conductances Are Impaired In Early Animal Diabetessupporting
confidence: 70%
“…It has been reported that the fast K + channel activity is reduced by 50% at cytoplasmic pH of 6.8 as a result of enhanced anaerobic glycolysis [24,48]. Decreased K channels could also explain our finding of membrane depolarization.…”
Section: Na and K Conductances Are Impaired In Early Animal Diabetessupporting
confidence: 70%
“…In the former, the magnitude of resistance appears to be related to the degree of medium-term metabolic control, rather than the presence or absence of neuropathy (Price et al, 1987). It has been suggested that increased resistance to hypoxia results from increased availability of substrate for anaerobic energy production in the diabetic nerve (Shirabe et al, 1988;Parry and Kohzu, 1990;Schneider et al, 1993). We cannot confirm this suggestion since values in this experiment did not correlate with either those for plasma or nerve glucose in diabetic rats.…”
Section: Discussionmentioning
confidence: 55%
“…The chain of events by which hyperglycaemia leads to nerve damage, predominantly in sensory fibres, is far from clear but there is much evidence that endoneurial hypoxia due to microangiopathy is involved (for review see Low, 1987;Thomas & Tomlinson, 1993). Using isolated frog nerves, Lorente de N6 (1947) first made the observation that high glucose concentrations cause a lack of functional recovery after hypoxia, and this phenomenon has recently been investigated in rat peripheral nerves and spinal roots in vitro (Strupp, Jund, Schneider & Grafe, 1991;Schneider, Jund, Nees & Grafe, 1992;Schneider, Niedermeier & Grafe, 1993a; Quasthoff, Mitrovic & Grafe, 1993 b). Recovery of membrane and action potentials from hyperglycaemic hypoxia is worse in dorsal than ventral roots (Schneider et al 1992), supporting an association with diabetic neuropathy.…”
mentioning
confidence: 99%
“…Recovery of membrane and action potentials from hyperglycaemic hypoxia is worse in dorsal than ventral roots (Schneider et al 1992), supporting an association with diabetic neuropathy. The poor recovery of dorsal roots is probably due to intracellular acidification by anaerobic glycolysis, since (a) it is worse when the buffering power and/or bicarbonatedependent pH-regulating mechanisms of the axons are compromised (Schneider et al 1992), (b) it only occurs with hexoses that can be metabolized rapidly by the glycolytic pathway (Schneider et al 1993a), and (c) it is associated with extracellular release of acid (Strupp et al 1991). It is a welldocumented observation that hypoxia and/or ischaemiainduced decrease in tissue pH is dependent on the preischaemic blood glucose concentration, being greatest in hyperglycaemic and least in hypoglycaemic animals (e.g.…”
mentioning
confidence: 99%